NORAD-regulated signaling pathways in breast cancer progression - Capela, Ana Maria (2024)
Long non-coding RNA activated by DNA damage (NORAD) has recently been associated with pathologic mechanisms underlying cancer progression. Due to NORAD's extended range of interacting partners, there has been contradictory data on its oncogenic or tumor suppressor roles in BC. This review will summarize the function of NORAD in different BC subtypes and how NORAD impacts crucial signaling pathways in this pathology. Through the preferential binding to pumilio (PUM) proteins PUM1 and PUM2, NORAD has been shown to be involved in the control of cell cycle, angiogenesis, mitosis, DNA replication and transcription and protein translation. More recently, NORAD has been associated with PUM-independent roles, accomplished by interacting with other ncRNAs, mRNAs and proteins. The intricate network of NORAD-mediated signaling pathways may provide insights into the potential design of novel unexplored strategies to overcome chemotherapy resistance in BC treatment.